2009
DOI: 10.1111/j.1600-0625.2008.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of a single variant allele (rs1426654) of the pigmentation‐related gene SLC24A5 in Greek subjects

Abstract: The SLC24A5 gene, the human orthologue of the zebrafish golden gene, has been shown to play a key role in human pigmentation. In this study, we investigate the prevalence of the variant allele rs1426654 in a selected sample of Greek subjects. Allele-specific polymerase chain reaction was performed in peripheral blood samples from 158 attendants of a dermatology outpatient service. The results were correlated with pigmentary traits and MC1R genotype. The vast majority of subjects (99%) were homozygous for the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(22 reference statements)
0
6
0
1
Order By: Relevance
“…This SNP also showed association with melanin levels in admixed African Americans and African Caribbeans, where carriers of the AG or GG genotypes had lighter skin than AA carriers did [133]. On the other hand, due to the allele fixation, this SNP is incapable to show any genetic association in Europeans, as was seen in studies using exclusively European samples [19,134]. A world-wide allele frequency map shows rs1426654 being highly polymorphic in South Asians (frequency A = 0.52) [135].…”
Section: Slc24a5mentioning
confidence: 77%
“…This SNP also showed association with melanin levels in admixed African Americans and African Caribbeans, where carriers of the AG or GG genotypes had lighter skin than AA carriers did [133]. On the other hand, due to the allele fixation, this SNP is incapable to show any genetic association in Europeans, as was seen in studies using exclusively European samples [19,134]. A world-wide allele frequency map shows rs1426654 being highly polymorphic in South Asians (frequency A = 0.52) [135].…”
Section: Slc24a5mentioning
confidence: 77%
“…To derive ancestry information from each individual, a panel of 41 ancestry-informative markers was genotyped, including FY and 36 short tandem repeats markers described in our previous studies,34,35 and augmented by 4 highly ancestry-informative SNPs, rs1540771 (6p23.5), rs1805007 ( MC1R ), rs12896399 ( SLC24A4 ), and rs1426654 ( SLC24A5 ), which are all associated with hair, eye, and/or skin pigmentation 36,37. These ancestry-informative markers were analyzed by a Bayesian cluster model using STRUCTURE software 38-40.…”
Section: Methodsmentioning
confidence: 99%
“…SLC24A5 is a gene already known to be involved in skin color determination for some time [29]. Moreover, rs1426654 locus explains per se the difference in skin melanin index between 25 and 38 % amongst people of European vs. West African ancestry, respectively [30][31][32]. Valenzuela et al identified rs1426654 and rs2424984, together with IrisPlex rs16891982, as being responsible for 45.7 % of the reflectance variance and an indicator of skin reflectance in human phenotypes across different populations [28].…”
Section: Introductionmentioning
confidence: 97%